If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(9k + -7) = 17 Reorder the terms: -8(-7 + 9k) = 17 (-7 * -8 + 9k * -8) = 17 (56 + -72k) = 17 Solving 56 + -72k = 17 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -72k = 17 + -56 Combine like terms: 56 + -56 = 0 0 + -72k = 17 + -56 -72k = 17 + -56 Combine like terms: 17 + -56 = -39 -72k = -39 Divide each side by '-72'. k = 0.5416666667 Simplifying k = 0.5416666667
| (-3x^3y/9y^2z)^-2 | | 8x+7+4x+43=180 | | 4(2x+6)-3=13x+21-5x | | 30=-5+16+3n | | -4=8-4w | | 5f-9+3=-35 | | 3x^2(x^2-7)=0 | | -81+3x=29-2x | | X=(40-2X) | | -8=3/8n | | -9(1+4d)=19 | | -12x-3y=-12 | | 55=4w-13 | | 3f-11=4 | | -8+9c=19 | | 1/4x=24-1/2x | | 8+9c=19 | | 4/5X1/3= | | -12x-12x^2=0 | | (Z+2)(9x-5)=0 | | 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 |